(Reseña) M. Isabel Lorca Martín de Villodres, "El jurista Diego Antonio Navarro Martín de Villodres (1759-1832) - Espinoza de los Monteros Sánchez, Javier (Historia, 2012)
Las "Reseñas bibliográficas" no contemplan resumen.